PENGEMBANGAN DAN PENDAMPINGAN APLIKASI RAPOR SANTRI BERBASIS WEBSITE DI PONDOK PESANTREN AL-IMAM AL-ISLAMI - Alifi, Muhammad Riza; Semiawan, Transmissia; Maspupah, Asri; Hayati, Hashri; Lieharyani, Djoko Cahyo Utomo (Universitas Mataram, 2024)
Al-Imam Al-Islami Islamic Boarding School (ponpes) located in Cikembar, Sukabumi, West Java is an educational institution. Al-Imam Al-Islam Islamic Boarding School has been established since 1994. One of the important activities at the Islamic boarding school is managing and issuing (generating) santri passports. Currently, Islamic boarding schools still experience several problems in managing and publishing report cards, including human error because they still use conventional methods using the Excel office application; and the process of issuing report cards is quite long because report card data is not stored in one place. Web application development is aimed at overcoming these problems, through the capability to minimize human error with management support in setting user access rights based on roles or assignments, centralized data storage, and support for the data recapitulation process to speed up the issuance of report cards. This application development method consists of nine stages, namely: (1) Problem Identification; (2) Literature Study; (3) Data Collection; (4) Needs Analysis; (5) Application Design; (6) Application Implementation; (7) Application Testing and Improvement; (8) Assistance in using the application; and (9) Preparation of Output Documentation. The result of this activity is an appropriate technology product in the form of a web application for managing and publishing Islamic boarding school report cards, accompanied by modules and handouts for users using instructions and technical management of the application. Based on test results and use by users, this application has made it easier for Islamic boarding schools to manage and publish Islamic boarding school report cards. As a community service activity, a web-based application for managing and publishing report cards has been adopted and utilized directly by Islamic boarding schools as user partners.